Describing Cultural Content in English Textbook - Martha Kumala; Jesica Yuni Lestari (Sintuwu Maroso Journal of English Teaching, 2021)
The purposes of this study are to find and describe cultural content in English textbooks based on the theory of cultural dimensions by Moran (2001). The data are taken from an English textbook entitled “When English Rings a Bell” revised 2017 for first year students of junior high school published by the Pusat Kurikulum and Perbukuan, Balitbang, Kemendikbud. There are 8 chapters that have been analyzed by the researcher. In this study, the researcher only focused on the part of the image to be studied and described. This study used descriptive qualitative method. The results of this study indicate that this textbook contains all sections of the categories of cultural dimensions based on Moran's (2001) theory, five cultural dimensions (product, person, practice, perspective, and communities). Based on these findings, the researcher recommends this book to be used as teaching material by English teachers, but the researcher suggests enriching references when teaching students.